2012
DOI: 10.1038/nchem.1301
|View full text |Cite
|
Sign up to set email alerts
|

A molecular ruthenium catalyst with water-oxidation activity comparable to that of photosystem II

Abstract: Across chemical disciplines, an interest in developing artificial water splitting to O(2) and H(2), driven by sunlight, has been motivated by the need for practical and environmentally friendly power generation without the consumption of fossil fuels. The central issue in light-driven water splitting is the efficiency of the water oxidation, which in the best-known catalysts falls short of the desired level by approximately two orders of magnitude. Here, we show that it is possible to close that 'two orders of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
1,285
3
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 1,194 publications
(1,331 citation statements)
references
References 26 publications
36
1,285
3
7
Order By: Relevance
“…31 is analogous to those depicted for various homogeneous catalyst systems. 316,323,324 This is not unexpected given the very dispersed and somewhat tenuous nature of the catalytically active hydrous oxide layer. A common feature of these reaction schemes is that the initial catalytic step involves the deprotonation of a metal coordinated water molecule.…”
Section: View Article Onlinementioning
confidence: 86%
“…31 is analogous to those depicted for various homogeneous catalyst systems. 316,323,324 This is not unexpected given the very dispersed and somewhat tenuous nature of the catalytically active hydrous oxide layer. A common feature of these reaction schemes is that the initial catalytic step involves the deprotonation of a metal coordinated water molecule.…”
Section: View Article Onlinementioning
confidence: 86%
“…18 A complete Pourbaix diagram is offered in Figure 2B where the zones of predominant species derived from 2 II (H2O) with different electron/proton content are shown. An interesting feature of the Pourbaix diagram for 2 IV (OH) + is the pH 10-14 zone, that has been built by extrapolating the values of the V/IV couple at this pH and by assuming that the redox potential for the Ru V =O/Ru IV =O couple for [Ru IV (bda)(Me-py)2(O) eq ], 3 IV (O) (1.12 V), 15 is the same as for 2 IV (O) (Me-py is 4-methylpyridine). This assumption is based on Lever's approach 22,23,24 where it is shown that the Ru III /Ru II couple for a set of complexes can be calculated based on additive contribution of their respective ligands bonded to the first coordination sphere.…”
Section: Redox Properties and Water Oxidation Catalysismentioning
confidence: 99%
“…4 Molecular transition metal complexes constitute an excellent platform to examine these factors since significant information based on an arsenal of spectroscopic, electrochemical and analytical techniques can be used together with the valuable complementary information provided by computational studies. 5,6,7,8,9,10,11,12,13,14 The best water oxidation catalysts reported today are based on seven coordinated Ru complexes containing dianionic ligands such as [2,2'-bipyridine]-6,6'-dicarboxylato (bda 2-) 15,16,17 and [2,2':6',2''-terpyridine]-6,6''-dicarboxylato (tda 2-) (see Figure 1 for drawn structures of these ligands). Particularly impressive is the seven coordinate complex [Ru IV (tda--N 3 O)(py)2(O) eq ], 4 IV (O), (the superscript in roman numbers indicates the formal oxidation state of Ru; py is pyridine; the "eq" superscript means equatorial) that is capable of oxidizing water to dioxygen at maximum turnover frequencies (TOFMAX) of 7,700 s -1 and 50,000 s -1 at pH = 7.0 and pH = 10.0 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] A photoelectrochemical solar fuel cell device combines the functions of light harvesting, charge separation and catalysis. [13][14][15] In the last decade several systems have been proposed employing either metal oxide nanoparticles 8,[16][17][18][19][20][21][22][23][24] or molecular complexes 8,[25][26][27][28] as water oxidation catalyst (WOC). Furthermore, the coupling between the WOC, the chromophore and an electron accepting semiconductor into a photoanode has been achieved through co-absorption of both the catalyst and the chromophore 16,[29][30][31][32] or through dye-WOC supramolecular complexes.…”
Section: Introductionmentioning
confidence: 99%